O curso de matemática da Pontifícia Universidade Católica de São Paulo: uma história de sua construção/desenvolvimento/legitimação - Ziccardi, Lydia Rossana Nocchi (2009)
The object of this study is the Course of Mathematics of the Pontifical University Catholic of São Paulo (PUC-SP): the trajectory of the course, its organization and academic structure, its accomplishments, its plans and projects that had involved administration, professors and students. We try to show the transformations that had occurred in the Course and in the Department of Mathematics of the PUC-SP, which had its origin in the concept that research is important in an institution focusing education, and which difficulties had appeared to integrate teaching and research. We present the early steps of Mathematics in Brazil, until the creation of the first universities and the first courses of Philosophy. We show PUC-SP conceived as an University since its birth until the implantation of the Center of Exact Sciences and Technology. We analyze the creation and the functioning of the Department of Mathematics and the Course of Mathematics of PUC-SP, both as undergraduate and graduate studies, and our research deals with primary and secondary sources, compared according to their temporal proximity. We analyze the relations between the course of Mathematics of PUC-SP and the course of Mathematics of the Faculty of Philosophy, Sciences and Letters of the University of São Paulo, mainly those inherent to the creation of the Course of Mathematics of PUC-SP. We present the curricula of the subjects of the Course of Mathematics of PUC-SP, throughout the years up to nowadays. We give special visibility to some mathematicians and educators responsible for the beginning of the course and focus their participation in the curricular development of the course. Moreover, we identify their contribution to the Course of Mathematics of PUC-SP and their personal achievements as researchers Mathematical Education